Parameterisasi Pengontrol Yang Menstabilkan Plant Secara Internal - Kasbawati Kasbawati (Department of Mathematics, Hasanuddin University, 2007)
This handing out lifts the problem about parameterization of all controllers that can internally stabilize the given system. Controller parameterization is done as a mean to show that the controller can we shape in so many kinds of parameter. A control problem in this setup is to analyze some specific properties (e.g., stability or performance) of the closed loop system or to design the feedback control K such that the closed loop system is stable in some appropriate sense.